An Adolescent with Incapacitating Tics - Kamal Nath; Subho Panja (Indian Journal of Private Psychiatry)
Introduction: Pediatric autoimmune neuropsychiatric disorders associated with streptococcal infections (PANDAS), also known as a pediatric acute-onset neuropsychiatric syndrome (PANS), are the sudden development of mainly obsessive–compulsive disorder (OCD) symptoms, tics, or other symptoms among children and adolescents. Case description: This case is about a male of age 15 years with a history of fever 3 years back, after which symptoms such as abnormal sounds and body movements gradually started, which were involuntary. After many trials with different antipsychotics, the patient started responding but symptoms persist along with anxiety and irritability at times. Conclusion: Pediatric autoimmune neuropsychiatric disorders associated with streptococcal infections occur in about 1 in 1,000 children, which is a rare disorder and is difficult to diagnose. The treatment is challenging as a suitable antipsychotic has to be picked in terms of efficacy and dosing.